Intracranial arteriovenous malformation and dural arteriovenous fistula embedded in a meningioma—case report and review of the literature - Moujahed Labidi; Geneviève Lapointe (Interdisciplinary Neurosurgery, 2015)
The association between a vascular malformation and a meningioma is a rare occurrence intracranially. We document the case of a 59-year-old man who presented with a right parietal extra-axial mass with headaches and seizures. Hemangiopericytoma was initially suspected on the basis of an unusual vascular pattern and rapid lesion progression. Angiography revealed abnormal vessels and an early draining vein associated with the mass. Arterial feeders were primarily from the middle cerebral artery with discrete contribution from both middle meningeal arteries. Craniotomy and Simpson 0 resection of the lesion were undertaken and revealed the coexistence of a dural based tumor with an AVM and a dural arteriovenous fistula (dAVF). Histology and immunohistochemistry were consistent with the diagnosis of meningioma and associated AVM. This case represents the eleventh report of an AVM associated with a meningioma, among which only 6 were contiguous. Such cases illustrate the pathogenic roles of angiogenesis and inflammation that is common to AVMs, dAVF and meningiomas.